IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA LEMBAGA KEUANGAN SYARIAH (PERBANKAN SYARIAH) (Mazahib, 2012)
Corporate Governance is a relatively new issue in the world of business management. Corporate governance is generally associated with the systems and mechanisms that govern relationships and create the right incentives among the parties interested in the company to achieve its business objectives optimally. Good corporate governance generally includes the application of the principles of transparency, accountability, fairness, and responsibility. Implementation of good corporate governance in Islamic financial institutions become increasingly important to do that foster trust within the community and improve the performance and progress of Islamic banking. GCG in the body of Islamic institutions is crucial to the development of Islamic banking towards the more advanced. In principle, the GCG implementation of relevant and in line with Islamic values. Islam requires that every aspect of life regulated by systems and structures that meet the best practices outlined by Allah SWT. Hence these two ideals must go hand in hand. GCG become an integral part of the Islamic concept of a full and thorough.